Rethinking Ethical and Social Education - Michelini , Maria-Chiara (Revista Letra Magna, 2022)
It is apparent that the social transformations of the last few decades, in turn swept and exasperated by the pandemic and the ongoing war, make it necessary to revaluate the social-ethical purposes of education in the context of these changes. As a result of these events, it is indisputable that the following existential dimensions of our society have a global and interdependent character: health, economy, politics, interpersonal relations, education, relationships between people, etc., which illustrate that these existential dimensions are interdependent and global in nature. The authors of this article argue for the necessity of revising the idea of social ethics education as a factor essential to human development. To begin with, they investigate the sense of connection between social ethics education and the other facets of human existence, such as politics and economics. The purpose of this contribution is to describe some crucial choices humanity faces when it comes to harnessing pedagogy to bring out its authoritative voice as a subject of cultural elaboration and a platform for training the next generation of teachers. The document proposes some guidelines within these frameworks for educational directions because it regards them as essential and in accordance with the perspective that has been outlined.